Study of sexual dimorphism of Malaysian crania: An important step in identification of the skeletal remains - Ibrahim A.; Alias A.; Nor F.M.; Swarhib M.; Abu Bakar S.N.; Das S. (Korean Association of Anatomists, 2024)
Indexed by Scopus